Traditional Values and Tetekon: Creativity and Innovation in Padalangan of Sundanese Wayang Golek Purwa - Marsel Ridky Maulana (Institut Seni Indonesia Yogyakarta, 2025)
Wayang golek purwa is one of the traditional art performances of the Sundanese community that has a standardized structure and tetekon in its performance. However, along with the times that affect the way of thinking of the performers of wayang golek purwa art, there are changes in function and structure that affect the tetekon of the previous wayang golek purwa performance. The purpose of this study is to examine the changes in the value of tetekon in the art of wayang golek purwa related to the development of creativity and innovation from the young generation of puppeteers. This research uses descriptive qualitative method through observation, audio-visual analysis of wayang golek performances, and literature study on wayang golek purwa puppetry. Based on these methods, it was found that there is a paradoxical phenomenon in wayang golek art: on the one hand, creativity plays an important role in maintaining the existence of wayang golek art, but on the other hand, it is often considered to violate tetekon or traditional rules. Tetekon needs to be interpreted not only as a standard rule, but as a principle that can provide space for creativity and innovation to maintain the relevance of wayang golek art.